Use of Trastuzumab for Neoadjuvant Therapy of HER2+ Breast Cancer - 5-Years of Experience in a Single Clinic - Zuazana, Bielčiková; Luboš, Petruželka; Renata, Chloupková (Klinicka onkologie, 2018)
BACKGROUND: Trastuzumab (Herceptin® - H) has been the standard-of-care for patients with HER2+ breast cancer (BC) since 2009 in the Czech Republic. Neoadjuvant application of H increases the number of patients who achieve pathological complete remission (pCR) and improves patients' outcomes. AIM: This study aimed to assess the effect of neoadjuvant therapy (NAT) with H in patients with early HER2+ BC and to correlate the therapeutic outcome with overall survival (OS). We defined pCR as no invasive carcinoma (ypT0) or in situ residual carcinoma (ypTis) in breast tissue and no invasive carcinoma in axillary lymphatic nodes (ypN0). To correlate pCR with the hormone dependency of BC, we compared the number of patients who achieved pCR between those with hormone-dependent (estrogen receptor (ER) +) BC and those with hormone-negative (ER-) BC. RESULTS: We evaluated data from 148 patients with HER2+ BC, most of whom were at stage II. Of these, 50.7% were premenopausal women and 45.9% had ER- BC. Most patients were treated with anthracyclines followed by taxanes and H. pCR was reported in 50% of patients (74/148). ER+ BC regressed more often to ypTis stage (24/35), ER- BC to ypT0ypN0 stage (26/39). The 1-year OS rate of patients who achieved pCR was significantly higher than that of patients who did not (100.0% vs. 95.3%, p = 0.009). Median OS was not achieved in pCR patients group. CONCLUSION: Patients who achieved pCR had a better prognosis than patients who did not. Key words: neoadjuvant therapy - trastuzumab - early breast cancer - pathological complete remission - prognosis The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers. Submitted: 14. 9. 2017 Accepted: 15. 2. 2018.
Keywords: Trastuzumab; Anthracyclines; neoadjuvantní terapie; Humans; Antineoplastic Agents, Immunological; Female; trastuzumab; receptor erbB-2; lidé; onkologická péče - zařízení; antracykliny; Breast Neoplasms; ženské pohlaví; prognóza; Czech Republic; Taxoids; taxoidy; Cancer Care Facilities; Neoadjuvant Therapy; nádory prsu; Receptor, ErbB-2; protinádorové látky imunologicky aktivní; Česká republika; Prognosis